CREDIT SAVING EFFORTS AFFECTED BY CORONA VIRUS DISEASE 2019 (COVID-19) THROUGH THE CREDIT RESTRUCTURE PROCESS. - Aprinisa (Progressive Law Review, 2020)
The pandemic over the Corona virus Disease 2019 (Covid-19) outbreak is engulfing the world which has left many people dead and all sides of human life affected. Not only is it life-threatening but the impact of the Covid-19 pandemic has also had a significant impact on the survival of the world economy and a country in particular. As a result of the Covid-19 pandemic, economic growth was hampered, business activities were forced to close so that there were many layoffs everywhere, the investment climate became sluggish, and people’s incomes were reduced even zero, resulting in the inability of people to meet their needs, especially for credit debtor customers. The impact of the Covid-19 pandemic has caused credit debtor customers to have difficulty carrying out their obligations to pay installments on loans or loans to banking institutions. At the current conditions, the bank in carrying out its operational activities is required to provide relief and policies to credit debtor customers directly affected from the Covid-19 pandemic and one of the efforts that can be made is the implementation of credit Restructure to maintain the health and correctness of the credit provided.